Desfechos obstétricos e perinatais associados à infecção pelo novo coronavírus durante a pandemia no Brasil: uma revisão integrativa - Nery, Helloise Barbosa (2022)
Postpartum depression (PPD), characterized as a mental and behavioral disorder associated with puerperal women, can now be seen as a public health problem given the alarming numbers worldwide. Currently, several studies are carried out with the aim of understanding whether there is an association between PPD and delay in child development, however these do not use standardized questionnaires or analyze the same maturation factors, in addition to using small samples and having relatively short follow-up periods. short. Thus, this study aimed to carry out an integrative review, seeking to systematize all cohort and case-control studies that dealt with the impact of postpartum depression on child development, published between January 2017 and January 2022. The research used studies available in five databases, namely PubMed, Scielo, Cochrane and LILACS, and a specific one in the field of psychology (APA – Psycinfo). According to the descriptors used, 222 (two hundred and twenty-two) studies were previously selected, and after reading them, using the exclusion factors, 19 (nineteen) remained. The adverse developmental outcomes present in the research revolved around specific domains, namely language, behavioral, emotional, physiological, social and psychomotor. It was possible to understand that the impact of postpartum depression in children does not follow linear paths, not always presenting the same results, but there is a significant influence in almost all domains of child development, with the exception of motor development. By carrying out this integrative review and thus systematizing the research, it will also be possible to think about factors and protective actions for the various stages of development affected by PPD.